Immobilization of tannery industrial sludge in ceramic membrane preparation and hydrophobic surface modification for application in atrazine remediation from water. Issue 10 (August 2019) - Mukherjee, Debarati; Kar, Susmita; Mandal, Arkaprava; Ghosh, Sourja; Majumdar, Swachchha
Abstract: Chromium laden waste produced from tannery industry was immobilized in ceramic matrix for fabrication of the tubular single channel microfiltration membranes by extrusion. The presence of chromia resulted in substitutional solid solution formation with alumina and catalyzed mullite phase growth, hence increasing the mechanical and chemical stability of the membranes. The structural, morphological and water permeation characteristics of the membranes were studied to analyze their formation mechanism and effect of different parameters, viz. the sintering temperature, amount of waste added, presence of organics and extent of chromium immobilization. The surface of the macroporous membrane was hydrophobically modified, by polydimethylsiloxane (PDMS), producing contact angle of 141°. The process efficiency of the hydrophobic membrane was assessed in terms of the removal of atrazine, a contaminant of emerging concern, following the principle of hydrophobic interaction. Effect of different operating parameters affecting atrazine removal, viz. transmembrane pressure, cross flow velocity and filtration time was studied in cross flow filtration mode. High atrazine removal of >95% was obtained along with the maintenance of high flux during the filtration operation. The prepared cost-effective microfiltration membranes can thus be further modified for efficient water treatment applications.